2016
DOI: 10.2214/ajr.15.15928
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Portal Vein Thrombosis (Neoplastic Versus Bland) on CT Images Using Software-Based Texture Analysis and Thrombus Density (Hounsfield Units)

Abstract: CT texture analysis and CT attenuation values allow reliable differentiation between neoplastic and bland thrombi on a single portal venous phase CT examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 32 publications
3
26
0
Order By: Relevance
“…Although there was no statistically difference in kurtosis and entropy, the values of them gradually increased as tumor malignant degree increased (from pNET to PDAC). This variation trend was in accordance with previous researches . Hence, this study could provide reference value for further large sample research and contribute to the development of CTTA.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although there was no statistically difference in kurtosis and entropy, the values of them gradually increased as tumor malignant degree increased (from pNET to PDAC). This variation trend was in accordance with previous researches . Hence, this study could provide reference value for further large sample research and contribute to the development of CTTA.…”
Section: Discussionsupporting
confidence: 91%
“…This variation trend was in accordance with previous researches. 26,27 Hence, this study could provide reference value for further large sample research and contribute to the development of CTTA. This study had several limitations.…”
Section: T a B L E 5 Comparison Of Area Undermentioning
confidence: 86%
“…Contrary to our initial concerns that GA-MRI may have a theoretical disadvantage in detecting PVTT owing to the decreased contrast between the portal vein and liver parenchyma arising from the early hepatocyte uptake of GA, as well as its lower gadolinium content [22,24,25], our study results demonstrated that GA-MRI better detected PVTT than CECT in HCC patients meeting the Milan criteria (p = 0.039 for both reviewers). This is in concordance with previous studies which reported a sensitivity of 81-93% using GA-MRI for the detection of PVTT [25] and of 48-86% using CECT [26,27,36]. This result may mainly be attributed to the better depiction of common imaging findings, such as continuity with the tumor in the adjacent liver parenchyma, and the additional contribution of diffusion-and T2-weighted imaging, which are not available with CECT.…”
Section: Discussionsupporting
confidence: 92%
“…Liver.-Another important imaging task is differentiating benign from malignant portal vein thrombus. Canellas et al (25) studied 117 patients with portal vein thrombus. They found that texture features including MPP and entropy had AUCs of 0.97 and 0.93, respectively, and 0.99 when combined, in differentiating bland (benign) thrombus from malignant (tumor) thrombus.…”
Section: Lesion Characterizationmentioning
confidence: 99%